Gender and Age. The Myth of Eternal youth in Advertising - Fobert Veutro, Maria Francesca (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2023)
As already observed in the 1970s by Simone de Beauvoir (La veillesse), it seems that the desire to appear younger than one’s age has become in contemporary society an actual “social duty” that needs to be fulfilled with the utmost commitment. This appears to be more important for women than for men. Therefore, the intersection of ageism and sexism can produce discrimination’s multiple forms, such as attaching a stigma to older women. This phenomenon can be studied through advertising, on the assumption that it is a reliable source of social values. In fact, in order to promote a product, advertisers propose easily recognizable values (such as youthfulness) relying also on a set of implicit values. Consumers may not perceive the latter; however, they are influenced by them, because they reflect assumptions assimilated since their primary socialization. Identifying those hidden values helps to critically consider stereotypes and imposed patterns. A corpus of documents on the fight against ageing, was examined for this research. The material consists of over 400 advertising images that appeared in weekly Italian magazines and some TV commercials broadcast by Italian and American networks. An intersectional approach and qualitative techniques of document analysis have been used, according to the principles of ethnographic content analysis (ECA) proposed by Altheide (1996). One general result is that the promotion of products that embody the manifest value of the aspiration to appear always young is mostly encapsulated in a few “definitions of the situation” (Thomas, 1931). These values – felt as familiar, reassuring and authoritative – convey the advertised message and induce people to buy the product. Some examples are: the uncritical faith in numbers; science and technology; the need to return to nature; the prestige deriving from exclusivity; the importance of rituals. Regarding the intersection between gender and age, the analysis highlights some gender-differentiated stereotypes and behaviour patterns. For example, the exclusion of sexuality in the life of women in old age, but not in that of men; or the fact that a woman’s life is punctuated by phases showing different threats to her appearance. These results are common to all the documents analysed, both Italian and American. However, other results – such as the willingness, or the reluctance, to mention death; and the disinhibition, or vice versa the disinclination, to ridicule the elderly – seem to show that there is a marketing difference between the two countries on these issues.